Antidiabetic efficacy of polar extracts of the leaves of Tetra cera indica Merr.(Dilleniaceae) in alloxanized rats - Ahmed, Qamar Uddin; S.Dogarai, Bashar Bello; Umar, Abdulrashid; Mat So'ad, Siti Zaiton (2011)
Plants are considered less toxic than synthetic drugs. Recently, the search for appropriate anti-diabetic agents has been focused on plants used in traditional medicine partly because of leads provided by traditional medicine to natural products that may be better treatment than currently used drugs responsible for serious side effects among diabetics. In folk remedies, leaves of Tetracera indica Merr.(Dilleniaceae) are effectively used in the treatment of diabetes. However, there is no scientific claim about its efficacy in the management of diabetes.